2020
DOI: 10.4314/tjpr.v19i1.23
|View full text |Cite
|
Sign up to set email alerts
|

Immunoprotective evaluation of <I>Escherichia coli</I> outer membrane protein A against the main pathogens of animal mastitis

Abstract: Purpose: To evaluate prokaryotic expression of the Escherichia coli (E. coli) outer membrane protein A (OmpA) and its immunoprotective function against the main pathogens of animal mastitis.Methods: A molecular cloning method was used to develop a prokaryotic strain expressing OmpA protein, which was purified by Ni-affinity  chromatography. Polyclonal antiserum was generated in mice immunized with OmpA protein. Enzyme-linked immunosorbent assay (ELISA) and western blotting were used to determine the titer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…S. aureus possesses a round shape for convenient counting and has been widely used in the analysis of leukocyte phagocytosis, is also a major etiologic agent of cow mastitis [ 1 ], and immunization with NP-OmpA may boost resistance to S. aureus infection. Moreover, we found that antiserum from animals immunized with NP-OmpA recognized with E. coli , which suggested that anti-NP-OmpA antibodies and E. coli formed antigen-antibody complexes and likely enhanced antigen presentation [ 15 ]. Antibodies from mice immunized with NP-OmpA also bound to OmpA at a higher titer (3200) than those from mice immunized with OmpA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. aureus possesses a round shape for convenient counting and has been widely used in the analysis of leukocyte phagocytosis, is also a major etiologic agent of cow mastitis [ 1 ], and immunization with NP-OmpA may boost resistance to S. aureus infection. Moreover, we found that antiserum from animals immunized with NP-OmpA recognized with E. coli , which suggested that anti-NP-OmpA antibodies and E. coli formed antigen-antibody complexes and likely enhanced antigen presentation [ 15 ]. Antibodies from mice immunized with NP-OmpA also bound to OmpA at a higher titer (3200) than those from mice immunized with OmpA.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-OmpA antibodies can regulate the function of specific phagocytosis to protect against E. coli infection [ 14 ]. We found that OmpA had significant protective rates of 58.33% and 46.15% against E. coli and Staphylococcus aureus, respectively, and the OmpA fragment is also immunogenic [ 15 ]. Therefore, OmpA is a vaccine candidate for the prevention of E. coli infection.…”
Section: Introductionmentioning
confidence: 99%
“…S. aureus is also a major causative agent of cow mastitis [1], and immunization with NP-OmpA may boost resistance to S. aureus infection. Moreover, we found that antiserum from animals immunized with NP-OmpA interacts with E. coli, which suggests that anti-NP-OmpA antibodies and E. coli formed antigen-antibody complexes and likely enhanced antigen presentation [15]. Also, antibodies from mice immunized with NP-OmpA bound to OmpA at a higher titer (1: 3200) than those from mice immunized with OmpA.…”
Section: Discussionmentioning
confidence: 81%
“…Anti-OmpA antibodies can regulate the function of speci c phagocytosis to protect against E. coli infection [14]. We found that OmpA had signi cant protective rates of 58.33% and 46.15% against E. coli and Staphylococcus aureus, respectively, the pathogenic bacteria of cow mastitis, and that the OmpA fragment is also immunogenic [15]. Therefore, OmpA is a vaccine candidate for the prevention of E. coli infection.…”
Section: Introductionmentioning
confidence: 84%
“…Then mice plasma was used for leukocyte phagocytosis analysis directly. In addition, the serum was harvested with 300 r/min centrifugation after 4℃ overnight for immunology analysis (Chen et al 2020).…”
Section: Preparation and Specific Analysis Of Polyclonal Antibodymentioning
confidence: 99%